Peningkatan Nilai Kopi Bajing Melalui Pelatihan Desain Kemasan di Pamanjur, Desa Girimoyo, Malang - Bhakti, Aditya Dwi Putra; Nasvian, Moch Fuad; Wibowo, Novin Farid Styo (Warta LPM, 2023)
Indonesia is on the path of the Bean Belt, which is an area suitable for the development of coffee trees. This makes Indonesia the fourth largest coffee producing country in the world with a production value of up to 12 million 60-kilo sacks by the end of 2020. Malang Regency, East Java, is one of the largest coffee bean producing regions in Indonesia. Squirrel coffee is a variant of coffee that comes from the rest of the coffee cherries consumed by squirrels. This process provides a distinctive taste and aroma for coffee lovers. The uniqueness of Bajing coffee has not been exploited by coffee farmers and Pamanjur. Even consumers are more likely to choose Arabica coffee than squirrel coffee, because they feel that the taste does not have a significant difference. As a result, the price of squirrel coffee is still unable to reach its full potential. The UMM Service Team assisted Girimoyo and Pamanjur Villages to Compile Product Value and packaging to increase the selling value of Bajing Coffee. Several steps were taken by the team to develop a program to strengthen the value of coffee squirrels in Girimoyo Village, including: holding a meeting with the owner of Pamanjur to obtain initial data, then the team tried to understand the flavor profile of coffee squirrels by conducting a taste test, then developing a program to strengthen the value of coffee squirrels through design. packaging, by changing the name of Bajing coffee to Belka coffee. The term "Belka" comes from the Russian language which is the name for the animal "Squirrel". After the concept matured, the team worked on a prototype of the Bajing coffee packaging. The final stage is the finalization and printing process carried out by Pamanjur. In conclusion, by taking advantage of the unique characteristics of Kopi Bajing and implementing an effective packaging design, Girimoyo Village can maximize the market potential of its specialty coffee.